Taymāʾ in the Nabataean kingdom and in "Provincia Arabia" - Tourtet, Francelin; Weigel, Friedrich (Proceedings of the Seminar for Arabian Studies, 2015)
The comparative analysis of architecture and pottery of the Nabataean and Roman periods from the central residential area of Taymāʾ (Areas E-South and F) enables an investigation of the impact of the annexation of the Nabataean kingdom by the Roman Empire at the level of the daily life of non-elite parts of the local society. During the Nabataean period (represented by occupation level F:4 of the residential area), the non-elite material culture shows a strong autochthonous character. The use of Nabataean architectural elements is not attested. Organizational principles, such as the division of the ground floor into small compartments and the construction of multi-storey buildings, rather find parallels in southern and western Arabia (al-Ukhdūd, Qaryat al-Fāw). Similarly, many pottery shapes can be paralleled with those in north-west Arabia, but not in the Nabataean heartland. Nabataean influence can, however, be identified in the pottery technology by the introduction of a new fabric, and in numerous coarse ware jars. Nabataean fine ware, and especially its painted version, is extremely rare. In the late Roman period (OL F:3), the integration of Taymāʾ into Provincia Arabia led to stronger ties with the southern Levant, as evidenced by the use of courtyards similar to those in houses in the Levant at this time. Considering the pottery, except for a specific jar type, the majority of the shapes have parallels in late Roman sites from the southern Levant. It thus seems that the integration of Taymä 3 into Provincia Arabia led to a reinforcement of ties with the north.